Increased thrombospondin-4 after nerve injury mediates disruption of intracellular calcium signaling in primary sensory neurons. (1st May 2017) - Guo, Yuan; Zhang, Zhiyong; Wu, Hsiang-en; Luo, Z. David; Hogan, Quinn H.; Pan, Bin
Abstract: Painful nerve injury disrupts Ca 2+ signaling in primary sensory neurons by elevating plasma membrane Ca 2+ -ATPase (PMCA) function and depressing sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) function, which decreases endoplasmic reticulum (ER) Ca 2+ stores and stimulates store-operated Ca 2+ entry (SOCE). The extracellular matrix glycoprotein thrombospondin-4 (TSP4), which is increased after painful nerve injury, decreases Ca 2+ current (ICa ) through high-voltage–activated Ca 2+ channels and increases ICa through low-voltage–activated Ca 2+ channels in dorsal root ganglion neurons, which are events similar to the effect of nerve injury. We therefore examined whether TSP4 plays a critical role in injury-induced disruption of intracellular Ca 2+ signaling. We found that TSP4 increases PMCA activity, inhibits SERCA, depletes ER Ca 2+ stores, and enhances store-operated Ca 2+ influx. Injury-induced changes of SERCA and PMCA function are attenuated in TSP4 knock-out mice. Effects of TSP4 on intracellular Ca 2+ signaling are attenuated in voltage-gated Ca 2+ channel α2 δ1 subunit (Cav α2 δ1 ) conditional knock-out mice and are also Protein Kinase C (PKC) signaling dependent. These findings suggest that TSP4 elevation may contribute to the pathogenesis of chronic pain following nerve injury by disrupting intracellular Ca 2+ signaling via interacting with the Cav α2 δ1 and the subsequent PKC signaling pathway. Controlling TSP4 mediated intracellular Ca 2+ signaling in peripheral sensory neurons may be a target for analgesic drug development for neuropathic pain. Highlights: Thrombospondin-4 (TSP4) inhibits sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) function. Effects of TSP4 on SERCA function are attenuated in voltage-gated Ca 2+ channel Cavα2 δ1 subunit knockout mice. Nerve injury-induced depression of SERCA function is attenuated in TSP4 knockout mice. Effects of TSP4 on SERCA function are dependent on protein kinase C signaling.